The Food Additive β-Caryophyllene Exerts Its Neuroprotective Effects Through the JAK2-STAT3-BACE1 Pathway - Zhang, Yujia; Huang, Qiaoyan; Wang, Sichen; Liao, Ziqian; Jin, Haichao; Huang, Shuo; Hong, Xiao; Liu, Yiming; Pang, Jie; Shen, Qing; Wang, Qingcheng; Li, Changyu; et al. (Frontiers in Aging Neuroscience, 2022)
Despite extensive research on Alzheimer’s disease (AD), its diagnosis and treatment remain challenging, and no effective therapies are currently available. Amyloid β (Aβ) extracellular plaques and intracellular neurofibrillary tangles are the histological characteristics of AD that have been directly linked to neuropathological events such as synaptic and neuronal cell loss. In this study, we explored whether the ‘JAK2-STAT3-BACE1’ pathway is involved in neuroprotection conferred by the food flavouring agent β-caryophyllene (BCP). PC-12 cells with overexpressed amyloid-β protein precursor (APP) were utilised to construct an AD model in vitro, which was then split into four groups, namely control, empty vector, APP overexpression, and BCP (5, 10 and 20 μM). CCK-8 was used to evaluate cell viability, immunofluorescence was utilised to examine synaptic morphology, and quantitative real-time polymerase chain reaction and western blot were used to examine gene and protein expression levels. The relative expression levels of JAK2, STAT3, and BACE1 mRNA in the transfected PC-12 cells were found to be significantly upregulated. The cell morphology altered dramatically 72 h after transfection, becoming rounder, with a decrease in cell number. BCP exhibited the potential to dramatically increase PC-12 cell viability while protecting cell morphology. BCP inhibited APP, JAK2, STAT3, BACE1 mRNA and BACE1 protein overexpression, as well as JAK2 and STAT3 hyperphosphorylation. Molecular docking simulated the docking of BCP with JAK2, STAT3, BACE1, CB2. And JAK2 was found to be the most stable protein. In conclusion, inhibition of the ‘JAK2-STAT3-BACE1’ signaling pathway may be one of the mechanisms through which BCP protects neurons and antagonises Aβ’s neurotoxicity.